Fair street space allocation: ethical principles and empirical insights. Issue 6 (1st November 2020) - Creutzig, Felix; Javaid, Aneeque; Soomauroo, Zakia; Lohrey, Steffen; Milojevic-Dupont, Nikola; Ramakrishnan, Anjali; Sethi, Mahendra; Liu, Lijing; Niamir, Leila; Bren d'Amour, Christopher; Weddige, Ulf; Lenzi, Dominic; et al.
ABSTRACT: Urban street space is increasingly contested. However, it is unclear what a fair street space allocation would look like. We develop a framework of ten ethical principles and three normative perspectives on street space – streets for transport, streets for sustainability, and streets as place – and discuss 14 derived street space allocation mechanisms. We contrast these ethically grounded allocation mechanisms with real-world allocation in 18 streets in Berlin. We find that car users, on average, had 3.5 times more space available than non-car users. While some allocation mechanisms are more plausible than others, none is without disputed normative implications. All of the ethical principles, however, suggest that on-street parking for cars is difficult to justify, and that cycling deserves more space. We argue that ethical principles should be systematically integrated into urban and transport planning.